2020
DOI: 10.1016/j.bjpt.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of posture, sex, and age on breathing pattern and chest wall motion in healthy subjects

Abstract: Objective: We evaluated the effects of posture, sex, and age on breathing pattern and chest wall motion during quiet breathing in healthy participants. Methods: Eighty-three participants aged 42.72 (SD = 21.74) years presenting normal pulmonary function were evaluated by optoelectronic plethysmography in the seated, inclined (with 45 • of trunk inclination), and supine positions. This method allowed to assess the chest wall in a three dimensional way considering the chest wall as three compartments: pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 36 publications
9
29
2
6
Order By: Relevance
“…In our equation for t I / t tot , sex has not been identified as a determining factor ( t I / t tot was predicted by age and height only). Using optoelectronic plethysmography (OEP) with 83 healthy adult subjects, M endes et al [ 25 ] reported that t I / t tot did not change with posture or sex, which confirms our finding. Furthermore, actual values reported for expected t I / t tot in healthy adults are broadly similar to ours, with T obin et al [ 22 ] and P arreira et al [ 24 ] reporting an average t I / t tot of approximately 0.42±0.03 and 0.39±0.04, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our equation for t I / t tot , sex has not been identified as a determining factor ( t I / t tot was predicted by age and height only). Using optoelectronic plethysmography (OEP) with 83 healthy adult subjects, M endes et al [ 25 ] reported that t I / t tot did not change with posture or sex, which confirms our finding. Furthermore, actual values reported for expected t I / t tot in healthy adults are broadly similar to ours, with T obin et al [ 22 ] and P arreira et al [ 24 ] reporting an average t I / t tot of approximately 0.42±0.03 and 0.39±0.04, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…[25] using Optoelectronic plethysmography with 83 healthy adult subjects, report that Ti/Ttot did not change with posture or sex which confirms our finding. Furthermore, actual values reported for expected Ti/Ttot in healthy adults are broadly similar to ours, with Tobin [22] and Parreira [25] reporting an average Ti/Ttot of approximately 0.42±0.03 and 0.39±0.04 respecitvely. Wilkens et.…”
Section: Respiratory Rate (Rr)supporting
confidence: 89%
See 1 more Smart Citation
“…Respiratory diseases are increasing rapidly and drastically, along with environmental pollution ( Verschakelen and Demedts, 1995 ; Mendes et al, 2020 ). Existing therapies for respiratory diseases are not highly effective; therefore, it is necessary to develop novel agents.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…4. The determination of the final ROI: Since there is a difference in the contribution of the motion of the thoracic compartment or the abdomen to TV among sex and ages [19], we developed a unique algorithm to obtain the proper position of the bottom of the ROI. The algorithm was as follows:…”
Section: (B)mentioning
confidence: 99%